True-Time-Delay Unit Cell for Ultra-Wideband Single- and Wideband Dual-Polarized Large Reflectarrays - Reza Shamsaee Malfajani; Karim Glatre; Jean-Jacques Laurin (IEEE Access)
This paper presents the design and experimental validation of novel ultra-wideband true-time-delay (TTD) reflectarray unit cells for large-scale antenna applications. Two configurations are proposed: a single-polarized unit cell and a dual-polarized unit cell, both utilizing aperture-coupled stacked microstrip circular patches. The single-polarized unit cell employs a parasitic patch, an hourglass-shaped aperture, and a fork-shaped delay line, achieving a linear phase range exceeding 1040° at 13.1 GHz with a phase error below 25° and a linear phase bandwidth of 53% (9.6–16.6 GHz). A reflectarray prototype demonstrates a 3-dB gain bandwidth of 44.4% (10.5–16.5 GHz), with cross-polarization below -30 dB, sidelobe levels better than −13.5 dB, and aperture efficiency up to 55%. The dual-polarized unit cell incorporates perpendicular bowtie-shaped apertures with fork-shaped feeds, enabling independent phase control for both polarizations with a phase range over 1140° at 12.6 GHz, a phase error below 40°, and a linear phase bandwidth of 32% (10.7–14.5 GHz). A dual-polarized reflectarray achieves a 3-dB gain bandwidth of 36.1%, maximum gains of 32 dBi and 31.75 dBi for orthogonal polarizations, cross-polarization below −26 dB, sidelobe levels below −13 dB, and aperture efficiency up to 50%. Both designs exhibit low loss, stable beam direction, and high scalability, significantly advancing wideband reflectarray performance for satellite and communication systems.